Potentiating the Activity of Nisin against Escherichia coli - Zhou, Liang; van Heel, Auke J.; Montalban-Lopez, Manuel; Kuipers, Oscar P. (Frontiers in Cell and Developmental Biology, 2016)
Lantibiotics are antimicrobial (methyl)lanthionine-containing peptides produced by various Gram-positive bacteria. The model lantibiotic, nisin, binds lipid II in the cell membrane. Additionally, after binding it can insert into the membrane creating a pore. Nisin can efficiently inhibit the growth of Gram-positive bacteria and resistance is rarely observed. However, the activity of lantibiotics is at least 100-fold lower against certain Gram-negative bacteria. This is caused by the fact that Gram-negative bacteria have an outer membrane that hinders the peptides to reach lipid II, which is located in the inner membrane. Improving the activity of lantibiotics against Gram-negative bacteria could be achieved if the outer membrane traversing efficiency is increased. Here, several anti-Gram-negative peptides (e.g., apidaecin 1b, oncocin), or parts thereof, were fused to the C-terminus of either a truncated version of nisin containing the first three/five rings or full length nisin. The activities of these fusion peptides were tested against Gram-negative pathogens. Our results showed that when an eight amino acids (PRPPHPRL) tail from apidaecin 1b was attached to nisin, the activity of nisin against Escherichia coli CECT101 was increased more than two times. This research presents a new and promising method to increase the anti-Gram-negative activity of lantibiotics.